Restaurant industry operations report. - Laventhol & Horwath; National Restaurant Association (U.S.). ([Washington, D.C.] National Restaurant Association, 1986)
Annual
Annual.
Based on financial and operating data provided by members of the National Restaurant Association.
Prepared in cooperation with Laventhol & Horwath.
Title from cover.
Keywords: Restaurants -- Statistics -- United States -- Periodicals